Toward an understanding of the emotional and behavioral reactions to stalking: a partial test of general strain theory - Ngo, Fawn T. (Crime & delinquency, 2016)
Using data from the Supplemental Victimization Survey and relying on theoretical direction provided by Agnew’s general strain theory, we examine whether specific types of stalking experiences trigger specific types of negative emotional states and whether specific negative emotional states are in turn associated with specific types of noncriminal coping mechanisms. We find that while several of the stalking experiences trigger a variety of negative emotional states, other stalking experiences do not exhibit any association with negative emotions. We also uncover that negative emotional states in response to strain can trigger legitimate coping mechanisms. One notable finding that emerged from our results is that feeling annoyed/angry is significantly associated with noncriminal coping strategies. The policy implications of our findings are also discussed.